A comparison of direct and indirect splits based on the energy costs - P. O. Mavletkulova; L. A. Serafimov; T. V. Arkhipova (Тонкие химические технологии, 2013)
The values of minimum reflux ratio for distillation of zeotropic ternary mixtures were calculated in case of direct and indirect splits. A comparative analysis of these regimes was carried out using the vapor flow criterion. Depending on the feed composition the areas of more favorable process organization were determined in a concentration simplex. It was concluded that when calculating of minimum reflux it is necessary to consider that the relative volatilities of components are not constant along the apparatus even for ideal mixtures.